The Correlation between Students’ Learning Motivation and Their Reading Comprehension at Madrasah Aliyah Negeri 1 Lombok Tengah in Academic Year 2024/2025 - Putri, Elinda Islami; Arifuddin, Arifuddin; Aziz, Atri Dewi; Lestari, Yuni Budi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
This research aims to analyze and describe the correlation between students’ learning motivation and their reading comprehension among eleventh-grade students at Madrasah Aliyah Negeri 1 Lombok Tengah in the academic year 2024/2025. This study employs a mixed-method approach, combining quantitative and qualitative data. The sample consisted of 39 students from the entire eleventh-grade population. Data were collected using questionnaires, reading tests, and interviews. Quantitative analysis using One-way ANOVA indicated a correlation between motivation levels (high, medium, low) and reading comprehension (p = 0.011< 0.05). Qualitative interviews supported the statistical findings by identifying intrinsic factors (to improve skill and knowledge, discover new vocab and feel satisfied, challenge, curiosity, interest, hobbies and trends) and extrinsic factors (academic needs, achievement grades, practical need, support from school and teacher) that influenced motivation.